Zero Trust Security for microservices in scalable systems - Silva, José Miguel de Jesus (2024)
In the dynamic landscape of contemporary cybersecurity, the Zero Trust model has emerged as a pivotal paradigm, revolutionizing conventional notions of network trust. This thesis undertakes a comprehensive exploration of key dimensions within Zero Trust implementation, encompassing the theoretical and practical evaluation of diverse technologies, real-world performance assessments, and an in-depth analysis of resource implications, regulatory alignment, and human-centric vulnerabilities. Through a nuanced investigation, this research contributes valuable insights to the ongoing discourse on cybersecurity, offering practical guidance for organizations navigating the challenges of modern computing environments. By addressing technology selection, performance in real-world scenarios, resource considerations, regulatory compliance, and human factors, this thesis aims to empower cybersecurity practitioners with a holistic understanding of the intricate dynamics surrounding Zero Trust security.